„Wzruszenie trwalsze niż ściany gmachów obróconych w gruz”. Między tradycją a nowoczesnością: Irzykowski wobec Żeromskiego - Panek, Sylwia (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
This paper shall discuss Karol Irzykowski’s views on the prose work of Stefan Żeromski. The shifting nature of the former towards the latter – author of Ludzie Bezdomni [The Homeless] 1899 – shall be examined; ones that changed from criticism to approval. In this context Irzykowski’s critical concept developed in his collection of essays, Czyn i słowo [Action and the Word] 1913, shall be taken into account and it shall also be argued that Irzykowski’s polemical discourse in respect to Żeromski was an integral part of his literary manifesto.